Ursolic acid treatment suppresses cuprizone-induced demyelination and motor dysfunction via upregulation of IGF-1 - Shinji Yamamoto; Chiaki Sakemoto; Kensuke Iwasa; Kei Maruyama; Kuniyoshi Shimizu; Keisuke Yoshikawa (Elsevier, 2020)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system, characterized by apoptotic death of mature oligodendrocytes, neuroinflammation, and motor dysfunction. A pentacyclic triterpenoid compound, ursolic acid (UA), has various pharmacological activities, such as anti-inflammatory, anti-oxidative, and anti-apoptotic effects. In the present study, we investigated the effects of UA on cuprizone-induced demyelination, which is a model of MS. Oral administration of UA effectively suppressed cuprizone-induced demyelination and motor dysfunction via the enhancement of IGF-1 levels in the demyelinating lesions. Our results suggest that UA might be therapeutically useful for demyelination in MS.